The development and validation of a patient-reported outcome measure to assess financial hardship among older cancer survivors in China: hardship and recovery with distress survey - Liu, Li; Zhang, Aihua; Su, Mingzhu; Sun, Xiaojie; Shao, Di; Cheng, Joyce; Yao, Nengliang (Aaron) (Frontiers in Oncology, 2023)
Background: Financial hardship has been described as a patient’s economic experience following cancer-related treatment. Standardized patient-reported outcome measures (PROM) to assess this distress has not been well-studied, especially among older cancer survivors. Objective: The aim of this study was to develop and validate PROM for assessing the financial hardship of older cancer survivors in China. Methods: Items were generated using qualitative interviews and literature review. Items were screened based on Delphi expert consultation and patients’ opinions. Item response theory (IRT) and classical test theory (CTT) were used to help reduce items. Retained items formed a pilot instrument that was subjected to psychometric testing. A cut-off score for the new instrument for predicting poor quality of life was identified by receiver operating characteristic (ROC) analysis. Results: Qualitative interviews and literature review generated 135 items, which were reduced to 60 items because of redundancy. Following Delphi expert consultation and patients’ evaluation, 24 items with high importance were extracted. Sixteen items were selected due to satisfactory statistical analysis based on CTT and IRT. Ten items were retained and comprised 2 domains after loadings in EFA. Internal consistency was satisfactory (α = 0.838). Test-retest reliability was good (intraclass correlation, 0.909). The ROC analysis suggested that the cut-off of 18.5 yielded an acceptable sensitivity and specificity. Conclusions: The PROM for Hardship And Recovery with Distress Survey (HARD) consists of 10 items that specifically reflect the experiences of financial hardship among older Chinese cancer survivors, and it also showed good reliability and validity in clinical settings.